Tindak Kelakar Sebagai Wacana Penutup dalam Rapat Dinas di MTs. Nurul Huda Banyuputih Batang: Kajian Pragmatik - Kusuma, Diah Nila, Prof. Dr. Harun Joko Prayitno, M.Hum, Prof. Dr. Markhamah, M.Hum (2015)
The objectives of the study are three. (1) To identify the types a joke act as a clossing discourse in official meetings at MTs. NHBB. (2) To describe the politeness principle deviations a joke act as a clossing discourse in official meetings at MTs. NHBB. (3) To implement the politeness of joke as teaching materials in SMP/MTs. The research is qualitative descriptive. The objects of the research are the jokes act as a clossing discourse in official meetings. The data collection method is simak method with the sadap basic technique and followed by teknik lanjutan simak libat cakap (SLC), simak bebas libat cakap (SBLC), rekam, and catat, the last method is teknik observasi. The technique in analizing applied by the sub reference of padan method and sub pragmatic of padan method. The results of the research are: (1) The types a joke act as WPRD in MTs. NHBB found the five basic of politeness, they are: assertive, directive, commissive, expressive, and declaration. The dominant speech acts is directive; (2) Deviations politeness prinsiple found three types, they are: tact maxim, generisity maxim, and approbation maxim; (3) The politeness a joke act can be implemented as teaching materials of Indonesian subjects in SMP/MTs ninth grade with the statement joke materials, the method use conversation or discussion, learning media use modeling, and evaluation process use speech acts.